An inorganic–organic hybrid crystal with a two-step dielectric response and thermochromic luminescence. Issue 7 (27th January 2017) - Duan, Hai-Bao; Yu, Shan-Shan; Liu, Shao-Xian; Zhang, Hui
Abstract : An iodoplumbate-based hybrid crystal [C2 -Apy][PbI3 ] (1 ) (C2 -Apy + = 1-ethyl-4-aminopyridinium) was synthesized and characterized structurally. Abstract : An iodoplumbate-based hybrid crystal [C2 -Apy][PbI3 ] (1 ) (C2 -Apy + = 1-ethyl-4-aminopyridinium) was synthesized and characterized structurally. Single crystal X-ray diffraction revealed that1 crystallizes in the orthorhombic system with the space group Pnma at 150 K. Inorganic components form straight and face-sharing octahedral [PbI3 ]∞ chains and organic components form C2 -Apy + cations that are incorporated into the space between the inorganic chains. A temperature-dependent single crystal structure indicates that there exists an order–disorder transition of the cation. The dynamic motion of the cation strongly influences the dielectric and emission features of1 .1 shows a two-step dielectric response. The first step dielectric response at a low frequency is caused by direct current conduction and electrode polarization which have been proved by impedance spectra. The second dielectric response at a high frequency (10 kHz to 10 MHz) is related to the order–disorder transition of the alkyl chain and the dynamic motion of pyridyl rings. In addition, 1 shows multi-band emission, and different emission bands show different trends with the temperature change, which makes1 exhibit thermochromic luminescence properties.